Start : punch fear in the face, escape average, do work that matters - Acuff, Jonathan M. (Lampo Press, 2013)
Over the last 100 years, the road to success for most everyone has been divided into five predictable stages: Learning, Editing, Mastering, Harvesting, and Guiding. While none of the stages can be skipped, they can be shortened and accelerated. There are only two paths in life: average and awesome. The average path is easy because all you have to do is nothing. The awesome path is more challenging, because things like fear only bother you when you do work that matters. Start gives readers practical, actionable insights to be more awesome, more often.